Hepatotoxicity of 3,4-methylenedioxyamphetamine and α-methyldopamine in isolated rat hepatocytes: formation of glutathione conjugates - Bastos, Maria de Lourdes (2021)
The amphetamine designer drugs 3,4-methylenedioxymethamphetamine (MDMA or "ecstasy") and its N-demethylated analogue 3,4-methylenedioxyamphetamine (MDA or "love") have been extensively used as recreational drugs of abuse. MDA itself is a main MDMA metabolite. MDMA abuse in humans has been associated with numerous reports of hepatocellular damage. Although MDMA undergoes extensive hepatic metabolism, the role of metabolites in MDMA-induced hepatotoxicity remains unclear. Thus, the aim of the present study was to evaluate the effects of MDA and alpha-methyldopamine (alpha-MeDA), a major metabolite of MDA, in freshly isolated rat hepatocyte suspensions. The cells were incubated with MDA or alpha-MeDA at final concentrations of 0.1, 0.2, 0.4, 0.8, or 1.6 mM for 3 h. The toxic effects induced following incubation of hepatocyte suspensions with these metabolites were evaluated by measuring cell viability, the extent of lipid peroxidation, levels of glutathione (GSH) and glutathione disulfide (GSSG), the formation of GSH conjugates, and the activities of GSSG reductase (GR), GSH peroxidase (GPX), and GSH S-transferase (GST). MDA induced a concentration- and time-dependent GSH depletion, but had a negligible effect on lipid peroxidation, cell viability, or on the activities of GR, GPX, and GST. In contrast, alpha-MeDA (1.6 mM, 3 h) induced a marked depletion of GSH accompanied by a loss on cell viability, and decreases in GR, GPX and GST activities, although no significant effect on lipid peroxidation was found. For both metabolites, GSH depletion was not accompanied by increases in GSSG levels; rather, 2-(glutathion- S-yl)-alpha-MeDA and 5-(glutathion- S-yl)-alpha-MeDA were identified by HPLC-DAD/EC within cells incubated with MDA or alpha-MeDA. The results provide evidence that one of the early consequences of MDMA metabolism is a disruption of thiol homeostasis, which may result in loss of protein function and the initiation of a cascade of events leading to cellular damage.